PENGUATAN LEGALITAS UMKM MELALUI PENDAFTARAN NIB-OSS: PROGRAM SOSIALISASI DAN PENDAMPINGAN DI DESA MALANG RAPAT - Aldo Syahputra; Cyndi Ardanya; Dinda Amaliya; Faturrohman Faturrohman; Quratu Salsabila; Rilda Peharni; Riska Rahmalia; Sandia Fatika; Shansan Thalia Jelika; Tiara Amanda; Gina Septiana (Universitas Mataram, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in village economic development, yet they still face legal challenges that hinder access to financing and markets. In Malang Rapat Village, 16 MSMEs were found to lack a Business Identification Number (NIB), preventing them from utilizing government programs. This situation indicates low business legality literacy. This program aims to improve understanding and facilitate NIB processing for MSMEs in Malang Rapat Village. The activity was held on August 26, 2025, involving 16 participants. The methods used included observation, outreach, and assistance with NIB registration through the Online Single Submission (OSS). The results of the activity showed an increase in participants' understanding of the importance of NIB as a form of business legality. Of the 16 participants, 10 (62.5%) already had a NIB, 4 (25%) successfully obtained an NIB through direct assistance, and 2 (12.5%) experienced delays due to technical issues with the OTP (Online Transaction Protocol). This legality provides legal protection, ease of access to financing, and opportunities to participate in government programs. Furthermore, NIB ownership is a crucial requirement for applying for halal certification, which can increase product competitiveness in the broader market. Intensive outreach and mentoring have proven effective in addressing digital literacy challenges and preparing MSMEs to be more competitive.